Social and health outcomes following upgrades to a national housing standard: a multilevel analysis of a five-wave repeated cross-sectional survey - Wouter Poortinga; Nikki Jones; Simon Lannon; Huw Jenkins (BMC, 2017)
Abstract Background While existing research indicates that housing improvements are associated with health improvements, less is known about the wider social and health benefits of meeting national housing standards, as well as those of their specific constituent measures. This study evaluates the impacts of a managed housing upgrade programme through a repeated cross-sectional survey design. Methods A five-wave repeated cross-sectional survey was conducted over a seven-year period from 2009 to 2016 (n = 2075; n = 2219; n = 2015; n = 1991; and n = 1709, respectively). The study followed a managed upgrade programme designed to meet a national social housing standard over an extended period. The data were analysed from a multilevel perspective to take account of the time-dependent nature of the observations and differences in socio-demographic composition. Results The installation of the majority of individual housing measures (new windows and doors; boilers; kitchens; bathrooms; electrics; loft insulation; and cavity/external wall insulation) were associated with improvements in several social (housing suitability, satisfaction, and quality; thermal comfort and household finances) and health (mental, respiratory and general health) outcomes; and analyses showed relationships between the number of measures installed and the total amount invested on the one hand and the social and health outcomes on the other. There were however a few exceptions. Most notably, the installation of cavity wall insulation was associated with poorer health outcomes, and did not lead to better social outcomes. Also, no association was found between the number of measures installed and respiratory health. Conclusions The study suggests that substantial housing investments through a managed upgrade programme may result in better social and health outcomes, and that the size of the improvements are proportionate to the number of measures installed and amount invested. However, there may be risks associated with specific measures; and more attention is needed for mechanical ventilation when upgrading energy efficiency of houses through fabric work. In addition to providing new evidence regarding the wider social and health outcomes, the study provides an analytical approach to evaluate upgrade programmes that are delivered over multiple years.